The orca (Orcinus orca) pituitary gland: an anatomical, immunohistochemical and ultrastructural analysis - Alonso-Almorox, Paula; Blanco, Alfonso; Fiorito, Carla; Gómez-Villamandos, Jose C.; Risalde, M. A.; Almunia, Javier; Fernández, Antonio (Frontiers in Neuroanatomy, 2025)
The pituitary gland is central to endocrine regulation in vertebrates, coordinating key physiological processes such as growth, reproduction, and stress responses. In cetaceans, and particularly in large odontocetes like orcas (Orcinus orca), understanding pituitary structure is essential for advancing neuroendocrine research and informing welfare and health assessments. Despite their ecological, cognitive, and conservation significance, detailed morphological studies of the orca pituitary gland remain scarce. In this study, we conducted a comprehensive structural and ultrastructural analysis of the orca pituitary gland using postmortem samples from four captive individuals. We combined computed tomography, histology, immunohistochemistry, and transmission electron microscopy to examine the gland’s anatomical organization and cellular composition. Our results reveal features consistent with other cetaceans as well as species-specific characteristics, including the distribution and morphology of endocrine cells within the adenohypophysis and neurohypophysis. These findings provide the first integrated anatomical and ultrastructural reference for the orca pituitary gland, offering valuable insights into cetacean neuroendocrinology and supporting improved species-specific welfare evaluation, health monitoring, and management practices for orcas under human care.